Implmenting A Modified Shared Tree Multicast O-Corman Protocol in Wireless Adhoc Network - Vanisrsee, K; V.S.K.Reddy, Dr; Sudarsanan, K (International Journal of Engineering and Technology, 2018)
A mobile Ad Hoc network is a Noinfrastructure networkand randomly moves nodes are presented .Multicasting support data forwarding, and thus it is suitable for MANETs.Implementingâ€™Multicast opportunistic cooperative routing in Mobile Ad Hoc Networkâ€™, (MANET) to improves the %PDR , and reduces the power consumption, multicast is meant for group communication. Multicasting sending copy of the information to all members in a group, it improves, the wireless link in a network.In an Ad Hoc network nodesare randomly distributed and free to fly without any existing infrastructure or infrastructure less administration. In the Networkeach node isfitted out with a single omnidirectional antennaand that multiple nodes are allowed, together their transmissions to take the advantages of spatial diversity to obtain energy savings.It is assumed that some nodes are not a member in a group, hence it does not receive transmission, and packet has be resent again. Where as in existing unicast transmission protocol for multiple hop network picked by multiple intermediate nodes,and only one receiver. Theprotocol performance is analyzed using the ns-2.32 network simulator.Â